5-aminolevulinic acid-induced fluorescence cystoscopy for photodynamic diagnosis of bladder tumors: Oral versus intravesical administration - Ziad Alnaieb; Elsawi Osman; Shima Medani (Urology Annals)
Objective: This retrospective study aimed at comparing orally administered 5-aminolevulinic acid (5-ALA) to the intravesical (IV) route for the in vivo photodynamic diagnosis (PDD), follow-up, and guided transurethral resection of bladder tumors. Materials and Methods: A comparative retrospective review was conducted on adult patients who underwent 5-ALA-assisted cystoscopy for bladder tumor detection. Participants were divided into Group A, who received oral (ALA onco) powder, while Group B received 5-ALA intravesically. A comprehensive assessment, including patient history, physical examination, cytological urine analysis, ultrasound, and computed tomography scans, was performed. The sensitivity and specificity of white light cystoscopy were compared to PDD cystoscopy using both 5-ALA administration routes. Furthermore, the diagnostic accuracy of the oral versus the intarvesical route was directly compared. The associated toxicities were also identified. Patients were further categorized based on the morphological presence of muscle invasion. A further subgroup statistical analysis for the nonmuscle invasive category was carried out. Chi-square test was used to calculate (P) value for statistical significance, while Cohen’s d was used to assess the effect size. The confidence interval (CI) was denoted as 95%. Results: A total of 88 participants were included. Group A comprised 10 patients (8 males, aged 40–70 years), while Group B included 78 patients (58 males, aged 29–75 years). Oral 5-ALA demonstrated a sensitivity of 96%, compared to 60% for white light with a statistically significant difference (P = 0.025) with (95% CI 0.201–0.519). In terms of specificity, oral 5-ALA was statistically superior at 94%, compared to 80% with P = 0.024 (95% CI 0.160–0.519). On the other hand, IV 5-ALA showed 85.12% sensitivity compared to 70% for white light, which is statistically significant (P = 0.021) and (95% CI 0.231–0.279). There was no difference between white light and IV 5 ALA with regard to specificity (50% for both). On direct comparison, there was a statistically significant difference in favor of the oral form in terms of specificity (P = 0.008) with (95% CI 0.256, 0.624), whereas the oral 5-ALA showed higher sensitivity with no statistical difference. PDD significantly outperformed white light in detecting nonmuscle-invasive tumors as it picked up 24% additional lesions. During 15–24 months of follow-up, no recurrence was observed in Group A, while 29 patients (approximately one-third) in Group B experienced recurrence. No significant adverse effects were reported. Patients with bilharzia-associated bladder carcinoma did not behave differently. Conclusion: PDD using oral 5-ALA demonstrated superior diagnostic accuracy compared to IV administration and white light cystoscopy along with lower recurrence rate, making it the preferable option while larger scale and more powered studies are awaited.